Laryngeal Radiation Fibrosis: A Case of Failed Awake Flexible Fibreoptic Intubation - Johannes M. Huitink; Lambert Zijp (Case Reports in Anesthesiology)
Awake fibreoptic intubation is accepted as the gold standard for intubation of patients with an anticipated difficult airway. Radiation fibrosis may cause difficulties during the intubation procedure. We present an unusual severe case of radiation induced changes to the larynx, with limited clinical symptoms, that caused failure of the fibreoptic intubation technique. A review of the known literature on radiation fibrosis and airway management is presented.